Hierarchical stability conditions for time-varying delay systems via an extended reciprocally convex quadratic inequality - Zeng, Hong-Bing; Lin, Hui-Chao; He, Yong; Teo, Kok-Lay; Wang, Wei (Journal of the Franklin Institute, 2020)
This paper studies the stability problems of linear systems with time-varying delays. Firstly, an extended reciprocally convex quadratic inequality and an improved quadratic function negative-determination condition are proposed. Based on the method proposed, some less conservative criteria are derived. Finally, a well-known numerical example is carried out to demonstrate the effectiveness and the merits of the proposed method.